Flow channel instrument following the model of the Bostwick consistometer - Miranda Zamora, William Rolando (2020)
In food technology, the consistency measurement of many thick or pasty products such as sauces or fruit or vegetable pastes is recorded. The problem in engineering lies in the design and construction of a flow device that allows evaluating the consistency of pasty or thick foods, for which it has actually been reformulated as an empirical flow channel device following the model of the “Bostwick consistometer” through the "Bostwick consistency", which is used by researchers to define technical terms, such as tomato sauce. The objective has been to design and build an instrument, where the thick or pasty food is released into a specially made channel and the distance that the food has slipped after a certain time interval is measured, usually 30 seconds; this gives the thick or pasty food “Bostwick consistency”, for example a tomato puree, B30 (Bostwick 30 seconds) can only be considered as tomato sauce as long as it has a Bostwick measurement of less than 30 cm at 20 ° C, according to government agencies. An instrument following the model of the Bostwick has been designed and built of stainless steel.